Wage losses among spouses of women with nonmetastatic breast cancer. Issue 5 (10th December 2019) - Humphries, Brittany; Lauzier, Sophie; Drolet, Mélanie; Coyle, Douglas; Mâsse, Benoît; Provencher, Louise; Robidoux, André; Maunsell, Elizabeth
Abstract : Background: The aim of this study was to evaluate the wage losses incurred by spouses of women with nonmetastatic breast cancer in the 6 months after the diagnosis. Methods: A prospective cohort study of spouses of women diagnosed with nonmetastatic breast cancer who were recruited in 8 hospitals in the province of Quebec (Canada) was performed. Information for estimating wage losses was collected by telephone interviews conducted 1 and 6 months after the diagnosis. Log‐binomial regressions were used to identify personal, medical, and employment characteristics associated with experiencing wage losses, and generalized linear models were used to identify characteristics associated with the proportion of usual wages lost. Results: Overall, 829 women (86% participation) and 406 spouses (75% participation) consented to participate. Among the 279 employed spouses, 78.5% experienced work absences because of breast cancer. Spouses were compensated for 66.3% of their salary on average during their absence. The median wage loss was $0 (mean, $1820) (2003 Canadian dollars). Spouses were more likely to experience losses if they were self‐employed or lived 50 km or farther from the hospital. Among spouses who experienced wage losses, those who were self‐employed or whose partners had invasive breast cancer lost a higher proportion of wages. Conclusions: Although spouses took some time off work, for many, the resulting wage losses were modest because of compensation received. Still, the types of compensation used may hide other forms of burden for families facing breast cancer. Abstract : Although 78.5% of spouses take time off work because of their partner's nonmetastatic breast cancer in the 6 months after her diagnosis, in many cases, the resulting wage losses are modest because of compensation received. However, certain subgroups, particularly spouses who are self‐employed and those whose partners have invasive breast cancer, experience more extensive wage losses.